PENGEMBANGAN DESA WISATA EKOLOGIS SEBAGAI PARIWISATA MINAT KHUSUS DI DESA BELOK SIDAN: (Studi Kasus Ekowisata Jempanang D’ Alas, Desa Belok Sidan, Kabupaten Badung Bali) - Kiskenda, Dewa Putu; Trimandala, Nyoman Agus (Universitas Pendidikan Ganesha, 2025)
Ecotourism of Jempanang D'alas is encouraging the number of tourist visits which are still considered not optimal. This research discusses the existing conditions and examines strengths and weaknesses as well as opportunities and threats to optimally formulate strategies and programs for the development of ecological tourism as special interest tourism in Jempaang D'alas, Belok Sidan Village. This study uses a quantitative and qualitative approach. Data collection was carried out by observation, in-depth interviews and questionnaires to 75 respondents in proportion to (1) the government (Head of Belok Sidan Village, Petang District) (2) Jempalang D'alas ecotourism managers and (3) Tourists. Data analysis was carried out using the SWOT and QSPM methods. Based on the SWOT analysis obtained alternative strategies that can be applied to the development of Ecotourism in Japan D'alas, namely (1) strategies for creating quality ecotourism products, (2) strategies for increasing promotion through the application of information technology, (3) strategies for developing HR competencies and ( 4) marketing strategy for ecotourism products for tourists staying in villas and tourist attractions in Belok Sidan Village and its surrounding